Experimental study of the Portevin-Le Chatelier effect under complex loading of Al-Mg alloy: procedure issues (Fracture and Structural Integrity, 2021)
The aim of this work is to solve the methodological issues of the experimental study of the nucleation and propagation of deformation bands due to the Portevin-Le Chatelier effect under conditions of complex loading. It is of interest to determine the boundaries of unstable plastic deformation of the AMg6 alloy under complex loading conditions. A technique for controlling the loading process with a given rate of deformation intensity of materials has been worked out. The results showed that short-term stops and unloading during loading influence on the value of critical deformation, at which the manifestation of the jerky flow begins. The evolution of inhomogeneous strain fields and local strain rates under conditions of manifestation of jerky flow during tension with torsion tests of Al-Mg alloy samples.
Keywords: Jerky flow; Portevin-Le Chatelier effect; Strain field; Plasticity; Digital image correlation technique; Aluminum-magnesium alloy